Sexual Dimorphism in the Abdominal Tergtes of Kempiola shankari Sinha and Agarwal (Orthoptera : Phalangopsidae) - Sinha, K. M. (Indian Forester, 1982)
The first abdominal tergite of Male K. shankari possesses thick sinuate posterior margin with two pairs of sensory patch and one pair of sensory patch on second abdominal tergite. Tenth abdominal tergite possesses two lateral projections.